IDENTIFIKASI BULLWHIP EFFECT PRODUK PMI PADA DISTRIBUTOR KALIMANTAN DI PT. AS PURWOSARI - Wijiningsih, Wijiningsih; Sulistiarini, Emma Budi; Tjahjono, Ngudi (Industrial Engineering Department, Faculty of Engineering, Universitas Brawijaya, 2014)
In the cigarette industry for meeting consumer needs not only provide good taste, but also the fulfillment of the availability of goods. It required a good coordination between related parties such as suppliers, factory, distributors, retailers, and so on. Parties involved in the procurement of raw materials to the distribution of products to consumers is known as the supply chain. Lack of coordination will lead to information distortion phenomenon called the bullwhip effect. PT. U.S. Purwosari a cigarette factory with one of its products is PMI and product distribution in Borneo. At PMI Product frequent urgent packaging materials resulting in subsequent orders and production delays. Based on these in this study to identify the presence of the bullwhip effect on PT. U.S. to calculate its value and find the cause.